Scleral buckle hemorrhagic cyst masquerading as an orbital tumor - Almeida DRP (Dove Medical Press, 2015)
David RP Almeida,1 Eric K Chin,1 H Culver Boldt,1 Vinit B Mahajan1,2 1Department of Ophthalmology and Visual Sciences; 2Omics Laboratory, University of Iowa Hospitals and Clinics, Iowa City, IA, USA Abstract: We present a case of a 41-year-old man who was referred for evaluation of a choroidal tumor with a remote history of scleral buckle placement for traumatic retinal detachment. Ocular imaging, echography, and magnetic resonance imaging could not rule out a neoplastic process so the patient was taken for surgical exploration where a hemorrhagic cyst was discovered. This is the first case in the literature of a silicone scleral buckle–associated hemorrhagic cyst presenting as orbital mass. Keywords: choroidal mass, choroidal lesion, choroidal melanoma, echography, optical coherence tomography, magnetic resonance imaging